Improving learning in large classes with online quizzes - Feliu, Elisenda (Improving University Science Teaching and Learning, 2023)
In this project I address the problem of teaching mathematics to a large class of first-year students in life sciences. I focus on the introduction of quizzes during the lectures (clickers) and online quizzes for self study. The motivation to introduce quizzes is discussed, the practical aspects of the implementation is presented, and their effect on the students’ learning is assessed.